HUBUNGAN ANTARA PENGETAHUAN GIZI SEIMBANG, AKTIVITAS FISIK DAN STATUS GIZI REMAJA - Yohannes Willihelm Saleky; Hikmah Isnaini Okvitasari; Pusparini; Mimin Aminah (Jurusan Gizi Poltekkes Kemenkes Bandung, 2022)
The prevalence of overnutrition among adolescents in Indonesia is elevating due to overeating and incativity. Adequate nutritional knowledge helps adolescents in choosing healthy foods and doing physical activities. This study aims to identify the relationship between knowledge of dietary guidelines, physical activity, and nutritional status of the students of SMA Negeri 1 Bandar Lampung. The study design used was cross-sectional design. The study was conducted in April 2022 with a total sample of 85 respondents which were recruited by using the simple random sampling technique. Data of dietary guidelines knowledge were collected by using a validity-and-reliability tested questionnaire and data of physical activity were collected by using IPAQ (International Physical Activity Questionnaire), while antropometric measurement was carried out to determine nutritional status. Chi-Square test and Fisher Exact test with 0.05 as the level of significancy were done in statistical analysis. The results show that majority of the students had inadequate knowledge of dietary guidelines (51.8%) and had heavy and moderate physical activity (42.4% and 41.2%). There was also 25.9% of overweight students. There were no significant relationship between knowledge of dietary guidelines and physical activity (p-value = 0.901) and knowledge of dietary guidelines and nutritional status (p = 0.451). Nevertheless, there was a significant relationship between physical activity and nutritional status (p=0.029). The education about 4 pillars of balanced nutrition, particularly